'I deserve a treat!': Justifications for indulgence undermine the translation of intentions into action. (15th July 2013) - Taylor, Cat; Webb, Thomas L.; Sheeran, Paschal
<x xml:space="preserve">Abstract</x> The present research explores how justifications for indulgence influence the translation of 'good' intentions into action. Three studies investigated the nature of such justifications and their relation to indulgence. Study 1 identified six ways that people justify indulgence to themselves – that they are deserving or curious, that the indulgence is an exception to the norm or can be compensated for later, or that the tempting food is available or irresistible. Study 2 showed that the use of justifications undermined participants' strong (but not weak) intentions to halve their consumption of a nominated high‐fat food. Study 3 found that priming the use of justifications increased the amount of chocolate that participants consumed in a subsequent, ostensibly unrelated, taste test. Again, justification use had a greater effect on participants with strong intentions to limit indulgence. Taken together, the studies suggest a new approach to understanding intention–behaviour discrepancies.